FROST INVESTIGATION 1944-1945. APPENDIX 6. REPORT ON PIERRE AIRFIELD, PIERRE, SOUTH DAKOTA. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The report covers a comprehensive investigation of moisture and density changes occurring in the various pavement subsurface elements during the period from early fall, 1944, through the spring thaw period in 1945, the measurement of heaving of the pavement caused by frost action; and the determination, by means of accelerated traffic tests, of the carrying capacity of the airfield pavements during and immediately after thaw. The investigation includes both flexible and rigid type pavements, with further investigations of conditions under turf surfaces and of soils in specially constructed test boxes. (Author) See also Appendix 5, AD-712 383 and Appendix 7, AD-712 389.